TECHNICAL TEACHERS’ AND INDUSTRIAL MANAGERS’ RATINGOF TEACHERS’ AND STUDENTS’ ACTIVITIES TOIMPROVEPRACTICAL SKILLS ACQUISITION BY TECHNICAL COLLEGESTUDENTS IN KWARA STATE (NAU Journal of Technology and Vocational Education, 2024)
Practical skills deficiency among technical college graduates is responsible for the alarming rates ofunemployment. This study aims to find out, from the rating of technical teachers and industrialmanagers, the strategies that could improve practical skills' acquisition in technical colleges in KwaraState. Two research questions and one hypothesis guided the study. The population comprised of 127technical teachers and 71 industrial managers. The population were considered manageable hence;there were no need to employ any sampling. Out of the 205 copies of the instrument sent out, 198copies were analyzed. The instrument for data collection was a structured questionnaire. Theinstrument was strategies for improving practical skills' acquisition by students in Technical Colleges(QERSIPSASTC) which was validated by three experts from the Department of TechnologyandVocational Education, Nnamdi Azikiwe University, Awka. Reliability co-efficient value yielded 0.85. The instrument was a five-points Likert scale type with six sections. Mean statistic was usedtoanswer the research question and t-test statistic was used to test the hypotheses at a 0.05 significancelevel. Results from the analysis of data showed that demonstration method impart practical skills tostudents. Results also revealed that government should always recruit qualified technical teachers toteach technical subjects. Result of t-test showed that there was a significance difference in the meanratings of technical teachers and industrial managers on the teaching activities that could improvepractical skills acquisition by technical students.
Keywords: Industrial Managers; Practical Skills Acquisition; Technical Colleges; Technical Teachers.